COVID-19 impacts the sexual function of women - N. V. Artymuk; M. N. Surina; A. V. Atalyan; M. Al-Jefout; E. V. Nekrasova (Фундаментальная и клиническая медицина)
Aim. Sexual function plays an important role in normal human life, along with sleep and food. As it is behind the main human motivations and can manifest itself in any phase of sexual activity or at any time of sexual life, the sexual function is considered as an important factor in determining the quality of life in adults. Here we aimed to estimate the influence of novel coronavirus disease (COVID-19) on the sexual function of women.Materials and Methods. Our study enrolled 364 women (17-59 years of age) who admitted to the gynecological units of Kemerovo (Russia). A Female Sexual Function Index (FSFI) questionnaire was used to assess the clinical manifestations of sexual dysfunctions. The key FSFI indicators include desire, arousal, lubrication, orgasm, and satisfaction before and during the COVID-19 pandemic, the number of sexual contacts, the age of the partner, the duration of the relationship and cohabitation, and the assumption to have sexual dysfunction.Results. The sample was divided into 6 age groups: < 17 years (n = 2), 18-29 years (n = 121), 30-39 years (n = 136), 40-49 years (n = 80), 50- 59 years (n = 25), and ≥ 60 years of age (n = 0). All examined parameters of sexual dysfunction have been impacted by the pandemic. In particular, we documented the reduced sexual arousal, lubrication, and satisfaction as well as increased pain during the sexual intercourse. Risk factors for the development of female sexual dysfunction were age of the sexual partner, the duration of the relationship, the frequency of sexual intercourse, and baseline psychological state.Conclusion. COVID-19 pandemic has been associated with the considerable impairment of the female sexual function.